Landslide warning system using AVR microcontroller - Mohd Saleh, Hariyanti (2007)
This project based on measuring movement of mass like soil or rock on top of high land then sent a warning. This is an embedded system thus using hardware and software designed to perform a specific function and direct to the personal computer. System build using microcontroller as detection circuit and data sent to Personal Computer (PC) for display. The landslide warning type divided to four depend on data, there are Normal, Warning 1, Warning2 and Danger.